Antarmuka piranti single channel analyzer (sca) melalui port paralel printer pada komputer jenis pc - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT One of the methods to analyze nuclear radiation is using. Single Channel Analyzer (SCA). The new models of SCA is in the form of interface card which is connected to the computer by plug it in the computer slot. This kind of card has disadvantages. Its portability level is low and the card take electricity power dirrectly through the host computer, so that the power load of the computer is increased. To eliminate these disadvantages, in this research has been designed a SCA interface which is connected via PC's printer parallel port. Implementation has been done modularly to determine the performance of the design product. Tests have been done using pulse generator to simulate pulse outcoming from radiation detection and measurement devices. The result show that the linearity of SCA channels is high, with nonlinearity 0.3%, frequency responses up to 1 Mhz and rise time response of input pulses up to 100 microsecond. The SCA can be operated in 2 modes, window/normal mode and integral mode.